2007
DOI: 10.1037/0278-7393.33.4.704
|View full text |Cite
|
Sign up to set email alerts
|

Expanding retrieval practice promotes short-term retention, but equally spaced retrieval enhances long-term retention.

Abstract: Expanding retrieval practice (T. K. Landauer & R. A. Bjork, 1978) is regarded as a superior technique for promoting long-term retention relative to equally spaced retrieval practice. In Experiments 1 and 2, the authors found that expanding retrieval practice of vocabulary word pairs produced short-term benefits 10 min after learning, conceptually replicating Landauer and Bjork's results. However, equally spaced retrieval produced superior retention 2 days later. This pattern occurred both with and without feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
310
5
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(334 citation statements)
references
References 68 publications
18
310
5
1
Order By: Relevance
“…Second, the spaced words were always studied first. Some studies found a better performance on the massed items than on the spaced items during practice (e.g., Karpicke & Roediger, 2007). In our study, we did not find this difference, which may indicate that spaced items gained some processing advantage due to being studied first.…”
Section: Discussioncontrasting
confidence: 84%
“…Second, the spaced words were always studied first. Some studies found a better performance on the massed items than on the spaced items during practice (e.g., Karpicke & Roediger, 2007). In our study, we did not find this difference, which may indicate that spaced items gained some processing advantage due to being studied first.…”
Section: Discussioncontrasting
confidence: 84%
“…[17][18][19] Many of these investigations used free recall formats to demonstrate retained information and learning. 9,12,[17][18][19][20] However, other laboratory and classroom-based investigations have documented that self-testing with multiple-choice questions American Journal of Pharmaceutical Education 2014; 78 (2) Article 32.…”
Section: Discussionmentioning
confidence: 99%
“…Within each mini-block, 8 of the 32 characters repeated 10 times. The trials were presented in mini-blocks to help control the inter-repetition interval (IRI) for each stimulus, a variable that has been shown to influence learning difficulty as well as retention of learning (Karpicke and Roediger, 2007). This design had an average IRI of eight trials, which our pilot data suggested would produce an appropriate level of difficulty for learning.…”
Section: Methodsmentioning
confidence: 99%